Intersections between migration, class, gender and generation - Gavazzo, Natalia (Instituto de Investigaciones Socioeconómicas, 2020)
This article is part of an ethnographic fieldwork with migrant families in a context of urban segregation, environmental degradation and social vulnerability such as the Reconquista Area in northwestern Greater Buenos Aires. It seeks to analyze intersectionally the dimensions of migration origin class, gender and generation from the testimonies of migrant women – internal and international – to account for the complex modes of stratification and social production of inequality and social mobility in the territory. Focusing on the heterogeneity of experiences and resources mobilized, it is intended to understand the ways in which they develop individual and community strategies to adapt to the environment and achieve a long-awaited upward social mobility. The objective is to understand that social mobility and class senses are also built from extra-economic capitals that women appropriate and use to improve their living conditions and those of their families.